News on Fake News – Media Portrayals of Fake News by Japanese News Media - John W. Cheng; Hitoshi Mitomo (International Telecommunications Society (ITS), 2018)
This study quantitatively examines how the term 'fake news' is being portrayed by the Japanese news media using semantic network analysis. It uses newspapers as the representative as they are still one of the most influential news media in Japan. The data set consists of 624 newspaper articles that contain the word 'fake news' in Japanese and its equivalents extracted from the five national Japanese newspapers between 2015 and 2017. The analysis results have revealed six main themes within the articles. They show that fake news is mainly portrayed as an American problem that it is mainly associated with 'news about the US President,' 'the Trump-Russian inquiry,' and the 'media reportage of the US President.' On top of that, fake news is also portrayed an 'informational problem' that affects society through 'human-Internet interaction' and it has some 'implications for Japan' as well.
Keywords: 330; fake news; media portrayal; news media; content analysis; semantic network analysis